The Last Fight of the Revenge - Raleigh, Walter, 1552?-1618; Newbolt, Henry John, Sir, 1862-1938; Brangwyn, Frank, 1867-1956 (Salt Lake City, UT : Project Gutenberg, 2021)
"The Last Fight of the Revenge" by Sir Walter Raleigh is a historical account written in the early 20th century, specifically in the 1900s. The book chronicles a notable maritime conflict involving the English ship Revenge during its valiant engagement against a significantly larger Spanish fleet. The work captures the themes of honor, bravery, and sacrifice, highlighting the legendary nature of this battle. The narrative centers around Sir Richard Grenville, the commander of the Revenge, as he defends his ship against overwhelming odds in a fierce battle near the Azores in 1591. Despite being outnumbered and outgunned, Grenville and his crew fight tenaciously for hours, demonstrating remarkable courage and resolve. The account details the tactics employed during the conflict, the harrowing conditions faced by the crew, and Grenville's determination to uphold his duty despite the inevitable outcome. The book ultimately serves to commemorate Grenville's heroism and the ship's legacy, portraying it as a symbol of English naval valor and endurance, even in defeat. (This is an automatically generated summary.)
Release date is 2021-12-17
deaurider, Charlie Howard, and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Great Britain -- History, Naval -- Tudors, 1485-1603; Flores, Battle of, Azores, 1591; Revenge (Galleon); Grenville, Richard, Sir, 1541?-1591